The skillet : 200+ simpler ways to make just about anything, from perfect meals to breads, desserts, and more (America's Test Kitchen, 2024)
The hardest-working pan in the kitchen gets its moment to shine. ATK pushes the limit with what you can make in a skillet with 200+ recipes and inventive techniques that will forever change how you sear steak, roast chicken, simmer pasta, even scramble eggs. Once you start cooking from this book you will look at your skillets with fresh eyes. A skillet can be a baking dish, a roasting pan, a saucepan, a pasta pot, a griddle, and more. With this collection of one-pan dishes you have a roadmap for cooking perfect meals, breads, even dessert.